The complex studying of Antarctic biota - V. P. Polishuk; I. Yu. Kostikov; N. Yu. Taran; V. M. Voitsitsky; I. G. Budzanivska; S. V. Khyzhnyak; V. M. Trokhymets (Ukrainian Antarctic Journal, 2009)
Results of five year period of Argentina islands region Antarctic biota complex investigations are described. There were described 41 algae new for the Galindez island biogeografical polygon territory. Check-list of terrestrial algae now consists of 57 species belongs to 3 phyla. 12 species from Chlorophytà and Bacillariophyta were described for snow and cryophilic communities from Uruguay and Galindez islands. The preliminary analysis of different chord animals' groups' phenological peculiarities were carry-out. 9 fish, 14 birds and 8 mammals' species were analyzed. Complex phenological investigations of terrestrial animals from bryophytic and soil substrata were carry-out for the first time. Virus antigens were detected in samples of Deschampcia àntarctica and bryophytes from Barbilophozia and Polytrichum genera. This viruses belongs to different taxonomical groups such as Tobacco mosaic virus(Tobamovirus), Cucumber green mottle mosaic virus (Tobamovirus), Cucumber mosaic virus (Bromoviridae, Cucumovirus), Tomato spotted wilt virus (Bunyaviridae, Tospovirus). Deschampsia àntarctica photosynthetic tissues samples investigations revealed high level of antioxidant systems on example of superoxide dismutase. Such activity shows Deschampsia àntarcticà high plasticity. Such peculiar properties of photosynthetic membranes of lipid-protein-pigment complexes structural and functional components are demonstration of active adaptive strategies to Antarctic  limitative factors. Identified similarities lipid metabolism of various species may be indicative of the existence of a common ancestral form, but some differences in levels of lipid metabolism – on the next stages of evolutionary divergence in relation to the formation of a unique set of adaptations to the harsh Antarctic conditions. These data, together with the data of morphological, anatomical, physiological, molecular studies may be useful in assessing the evolutionary relationship of various species of Antarctic fish.